If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -9 = x(3) + -8 Reorder the terms: -9 + X = x(3) + -8 Reorder the terms for easier multiplication: -9 + X = 3x + -8 Reorder the terms: -9 + X = -8 + 3x Solving -9 + X = -8 + 3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + X = -8 + 9 + 3x Combine like terms: -9 + 9 = 0 0 + X = -8 + 9 + 3x X = -8 + 9 + 3x Combine like terms: -8 + 9 = 1 X = 1 + 3x Simplifying X = 1 + 3x
| 60x=46.6597 | | 2(90)-9=180-y | | 10(4x+2)=20(6) | | x*60=59.409 | | Y=180-9 | | 90=2(90)-18 | | 40(x-20)=40(3) | | 90=180-y | | 7x^5-33x^4+3x+52=0 | | 4x^2-3=1x | | 16a-263a=b | | 90-y=(2y)-18 | | x^7+5x^3+x-4=0 | | 16t-263t=h | | x^5-6x^3-16x=0 | | 7x^6+15x^2+1=0 | | 14x^2-5/7x | | 180-y=(3y)+56 | | log21x=2/3 | | 180-y=(3y)+44 | | x*60=72.1414 | | 27 = w8 | | 5(-4x-7)-5=-100 | | 54=9k | | s=10(4) | | 10x+32=72 | | x*0.06=72.1414 | | X+5+67=90 | | 2x-29+3x-21=180 | | 72=9d | | 4x+41=149 | | 42/[2*(17-13)-1] |